Online Assessment of Students An experience of CIET Online course on Action Research in Educational Technology - Pal, Rajendra (JOURNAL OF INDIAN EDUCATION, 2013)
The adoption of on-line assessment may help to manage large volumes of marking and assessment-related administration efficiently. The automation of routine online tasks may have the potential in the long-term to provide time and cost-efficient student assessment. The present evidence of Action Research course conducted at CIET advocate that on-line assessment can help significantly to the teachers.